2004
DOI: 10.1111/j.1365-2389.2004.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of N2O from farmed peat soils in Finland

Abstract: Agricultural peat soils are important sources of nitrous oxide (N 2 O). Emissions of N 2 O were measured from field plots of grass, barley, potatoes and fallow on a peat field in northern Finland during -2002 and in southern Finland in 1999-2002 In the north the mean annual fluxes of N 2 O (with their standard errors) during 2 years were 4.0 (AE1.2), 13 (AE3.0) and 4.4 (AE0.8) kg N ha À1 from the plots of grass, barley and fallow, respectively. In the north there were no significant thaw periods in the middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 18 publications
5
83
2
Order By: Relevance
“…The lower carbon density of the 30-40 cm layer in Majnegården soil compared with the topsoil resulted in lower emission rates in the incubation study. The higher degree of decomposition in the topsoil from Örke than in the Majnegården topsoil indicates a more disintegrated organic material that might decompose more easily (Regina et al, 2004). The Örke soil was better aerated at low tensions, which also could explain the higher CO 2 emission rates from this soil ( Figure 6).…”
Section: Effect Of Soil Type On Emission Ratesmentioning
confidence: 96%
See 4 more Smart Citations
“…The lower carbon density of the 30-40 cm layer in Majnegården soil compared with the topsoil resulted in lower emission rates in the incubation study. The higher degree of decomposition in the topsoil from Örke than in the Majnegården topsoil indicates a more disintegrated organic material that might decompose more easily (Regina et al, 2004). The Örke soil was better aerated at low tensions, which also could explain the higher CO 2 emission rates from this soil ( Figure 6).…”
Section: Effect Of Soil Type On Emission Ratesmentioning
confidence: 96%
“…N 2 O emissions peaked during spring ( Figure 5), maybe due to the production of easily available nitrogen for micro-organisms by freeze-thaw cycles in winter (Regina et al, 2004), combined with the absence of plants competing for nitrogen. It is often reported that N 2 O emissions can be very erratic, characterized by high emissions during short time periods (Flessa et al, 1998) and with peaks during spring after thawing or during winter (Maljanen et al, 2003a;Regina et al, 2004).…”
Section: Effect Of Soil Type On Emission Ratesmentioning
confidence: 99%
See 3 more Smart Citations